Cross-Sectoral Collaboration in the Free Nutritional Meal Program in Indonesia - Angga Prabowo; Ghina Ghaliya (Ikatan Sarjana Komunikasi Indonesia, 2025)
Malnutrition, particularly stunting, remains a critical public health challenge in Indonesia, prompting the government to launch the Free Nutritious Meals Program (MBG) as a strategic intervention. However, the program encounters significant implementation obstacles, including bureaucratic fragmentation and suboptimal inter-agency coordination. This study aims to analyze the mechanisms of cross-sectoral collaboration, identify supporting and inhibiting factors, and evaluate their impact on the program's effectiveness and sustainability. Utilizing an interpretive qualitative paradigm and a case study approach, data were collected through participatory observation and in-depth interviews with key strategic informants from the National Nutrition Agency (BGN) and crisis communication practitioners. The research applies the frameworks of Collaborative Governance (Ansell & Gash) and the Agency Network/Cluster Model to interpret the findings. The results indicate that the MBG program successfully integrates collaborative elements, such as a conducive policy context and active stakeholder engagement with a horizontal network architecture. This structure connects central actors to local clusters, enabling adaptive responses to crises and logistical challenges in remote areas. The study concludes that combining collaborative processes with a flexible network structure creates a resilient communication model that relies on horizontal synergy rather than vertical hierarchy to ensure sustainable nutrition enhancement.